Music for clarinet, bass clarinet, basset-horn with Suzanne Stephens - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 1994)
LAUB und REGEN / LEAVES and RAIN for clarinet and violaTIERKREIS / ZODIAC for clarinet and piano LIBRA for bass clarinet and electronic musicIN FREUNDSCHAFT / IN FRIENDSHIP for basset-hornTANZE LUZEFA! / DANCE LUCEFA! for basset-horn BIJOU for alto flute, bass clarinet and tapeMONDEVA/ MOON-EVE for tenor and basset-horn MISSION und HIMMELFAHRT /MISSION and ASCENSION for trumpet and basset-horn Xi for basset-hornWOCHENKREIS / CIRCLE OF THE WEEK for basset-horn and elec. keyboard instrumentsEVAs SPIEGEL / EVE'S MIRROR for basset-horn SUSANI for basset-hornYPSILON for basset-horn SUKAT for basset-horn and alto fluteFREIA for basset-horn.......